A child of uprootedness and transplantation: Japanese American literature and its road to ethnic recognition - Jarmołowicz‐Dziekońska, Małgorzata (Orbis litterarum, 2025)
This paper, focusing on the development of Japanese American literature, explores autobiography and memoir both as genres and a tangible means of coming to terms with one's own identity, which has enabled Japanese American authors to find their locus in American society. The sociohistorical context embedded in their literary works provides a springboard for the exploration of deeply rooted resentment and, at the same time, great resilience in the face of prejudice and discrimination. Japanese immigrants and their immediate descendants managed to use their discriminatory experiences and hardships suffered in the United States (especially during World War II) to their advantage and to forge a literary testimony abundant in confessions on excavating their past and negotiating their Japanese American identity.